Mediação da informação através de plataformas digitais: prática nas bibliotecas arquivos e museus da área metropolitana do Porto - Farias, Dayane dos Santos (2019)
The main goal of this study was to investigate how mediation occurs through digital platforms managed by libraries, archives, and museums within the metropolitan area of Porto. This study was applied in the 17 municipalities of the metropolitan area of Porto. This was an exploratory and descriptive research with a qualitative and quantitative approach. Our findings suggest that the increase and improvements of the library and archive services concerning digital technologies need to be revised and the engagement of trained professionals to be responsible for the mediation through digital platforms is required. Therefore, the integration between the digital environment and human resources is necessary for improving the mediation of the information within these services.